2020
DOI: 10.3390/ijerph17093164
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome in Occupational Therapists in Spain: Prevalence and Risk Factors

Abstract: The objective of this study was to assess the potential levels of burnout syndrome in occupational therapists in Spain, as well as the risk factors involved in its prevalence. The data were obtained through an online survey. The tool utilised for this purpose was the Maslach Burnout Inventory General Survey (MBI-GS) that takes into consideration the following dimensions: emotional fatigue, depersonalisation and reduction of personal satisfaction. A sociodemographic questionnaire was also utilised. The sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
4
28
0
4
Order By: Relevance
“…These findings are in accord with the results of a meta-analysis on burnout among mental health professionals (O'Connor et al, 2018) that suggested that role clarity, professional autonomy, a sense of fair treatment, and access to regular clinical supervision may support workers. Although direct evidence is needed, these factors, in addition to reduced workload and enhanced communication, can be significant in preventing burnout among occupational therapists (Escudero-Escudero et al, 2020). In our study, in prefectures under specific cautions, sufficient information from the workplace significantly reduced insomnia risk, whereas in other areas it significantly reduced depression risk.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These findings are in accord with the results of a meta-analysis on burnout among mental health professionals (O'Connor et al, 2018) that suggested that role clarity, professional autonomy, a sense of fair treatment, and access to regular clinical supervision may support workers. Although direct evidence is needed, these factors, in addition to reduced workload and enhanced communication, can be significant in preventing burnout among occupational therapists (Escudero-Escudero et al, 2020). In our study, in prefectures under specific cautions, sufficient information from the workplace significantly reduced insomnia risk, whereas in other areas it significantly reduced depression risk.…”
Section: Discussionmentioning
confidence: 62%
“…Occupational therapists are typically classified as second-line medical workers and do not directly care for people with COVID-19 during the acute phase. However, they have direct contact with their clients during treatment programs, which can increase their infection risk and have a negative impact on their mental health (Ito & Ishioka, 2020) negative psychological effects can affect care quality and lead to client dissatisfaction (Escudero-Escudero et al, 2020). To prevent or mitigate negative psychological effects on occupational therapists that can harm care quality, treatment programs and environments with effective infection prevention need to be established.…”
mentioning
confidence: 99%
“…Frequencies (n), percentages (%), average scores (M), and standard deviation (SD) were used to analyze the DCSQ at item and subscale levels. To calculate the level of job strain, the different scales were dichotomized into low and high based on the following cut-offs: demand scale (low 5-13 points and high 14-20), control scale (low 6-18 and high [19][20][21][22][23][24] and support scale (low 6-19 and high [20][21][22][23][24], in keeping with the study by Sleman and Vuleta [31].…”
Section: Methodsmentioning
confidence: 99%
“…Occupational therapists with less than 10 years of work experience have been found to be at higher risk of work-related stress symptoms due to psychosocial factors in the work environment than occupational therapy colleagues with longer work experience [20]. Additionally, being under 30 years of age has been found to be associated with an increased prevalence of burnout syndrome in occupational therapists [21]. According to Smith and Pilling [22], the transition from student to a health care professional may be stressful and challenging when having to manage a full caseload, take complete responsibility for clients and time management, take personal responsibility even when confidence is low, and is struggling to develop professional expertise.…”
Section: Introductionmentioning
confidence: 99%
“…A SB se manifesta em três dimensões: exaustão emocional, despersonalização e a baixa realização profissional (Amor, Baños & Sentí, 2020;Huarcaya-Victoria & Calle-Gonzáles, 2020), por meio de sintomas físicos, psíquicos, comportamentais e defensivos (Gerber, Scriba, Geissler, Reckling, Fischer, Karl & Benrath, 2020;Escudero-Escudero, Segura-Fragoso & Cantero-Garlito, 2020). A dimensão exaustão emocional pode ser entendida como a sensação de que os recursos físicos e emocionais de um indivíduo se esgotaram decorrente da sobrecarga de trabalho.…”
Section: Concepções Teóricas Sobre Sbunclassified